Animal model for high consumption and preference of ethanol and its interplay with high sugar and butter diet, behavior, and neuroimmune system - Moreira-Júnior, Renato Elias; Guimarães, Mauro Andrade de Freitas; Etcheverria da Silva, Miguel; Maioli, Tatiani Uceli; Faria, Ana Maria Caetano; Brunialti-Godard, Ana Lúcia (Frontiers in Nutrition, 2023)
Mechanisms that dictate the preference for ethanol and its addiction are not only restricted to the central nervous system, but also affects the immune system, which in turn interacts with the CNS, triggering neuronal responses and changes, resulting in dependence on the drug. In the striatum the interaction of the immune response and the transcriptional profile of some genes associated with loss of control and addiction to ethanol may influence the alcohol consumption and preference. The present study aimed to assess whether alcohol consumption affects the transcriptional regulation, neuroinflammation, and behavior and their interconnections. Males C57BL/6 mice, Il6 and Nfat knockouts were subjected to a protocol of high fat and sugar diet intake and free choice of ethanol in the following stages: T1 ‒ Dietary treatment, for 8 weeks, the animals receive high-calorie diet, High Sugar and Butter, or standard diet, American Institute of Nutrition 93-Growth; and T2 ‒ Ethanol consumption, animals are submitted, for 4 weeks, to alcohol within the free choice paradigm, being each of them divided into ten groups, four groups continued with the same diet and in the other six the HSB diet is substituted by the AIN93G diet. Five groups had access to only water, while the five others had a free choice between water and a 10% ethanol solution. Weight was evaluated weekly and consumption of water and ethanol daily. At the end of the experiment, Anxiety-like behavior and compulsive-like behavior were evaluated, transcriptional regulation of genes Lrrk2, Tlr4, Nfat, Drd1, Drd2, Il6, Il1β, Il10 and iNOS by RT-qPCR, and inflammatory markers by flow cytometry. Animals that the diet was replaced had an ethanol high preference and consumption, resulted in (1) elevation of inflammatory cells in the brain, (2) upregulation of genes associated with cytokines (Il6 and Il1β) and pro-inflammatory signals (iNOS and Nfat), downregulation of anti-inflammatory cytokine (Il10), dopamine receptor (Drd2) and the Lrrk2 gene in the striatum, and (3) decreased anxiety-like behavior, and increased compulsive-like behavior. Our findings suggest that interactions between the immune system, behavior, and transcriptional profile of the Lrrk2 gene influence the ethanol preferential and abusive consumption.